2016
DOI: 10.3389/fpls.2016.01653
|View full text |Cite
|
Sign up to set email alerts
|

Insights from the Cold Transcriptome and Metabolome of Dendrobium officinale: Global Reprogramming of Metabolic and Gene Regulation Networks during Cold Acclimation

Abstract: Plant cold acclimation (CA) is a genetically complex phenomenon involving gene regulation and expression. Little is known about the cascading pattern of gene regulatroy network and the link between genes and metabolites during CA. Dendrobium officinale (DOKM) is an important medicinal and ornamental plant and hypersensitive to low temperature. Here, we used the large scale metabolomic and transcriptomic technologies to reveal the response to CA in DOKM seedlings based on the physiological profile analyses. Low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 84 publications
1
77
0
Order By: Relevance
“…The reductions in metabolite levels observed at low temperature for both DA populations were considerably different to the changes displayed by TA (Figure ), as well as those reported for other species (Angelcheva et al, ; Cook, Fowler, Fiehn, & Thomashow, ; Wu, Jiang, Chen, Mantri, & Tao, ; Zhang et al, ). For this reason, we compiled a dataset based on eight studies comparing the metabolome performance in plants growing at optimum and low temperatures.…”
Section: Resultssupporting
confidence: 65%
“…The reductions in metabolite levels observed at low temperature for both DA populations were considerably different to the changes displayed by TA (Figure ), as well as those reported for other species (Angelcheva et al, ; Cook, Fowler, Fiehn, & Thomashow, ; Wu, Jiang, Chen, Mantri, & Tao, ; Zhang et al, ). For this reason, we compiled a dataset based on eight studies comparing the metabolome performance in plants growing at optimum and low temperatures.…”
Section: Resultssupporting
confidence: 65%
“…“MAPK signaling pathway” and “cAMP signaling pathway” were also enriched. Previously, it was reported that different protein kinase families (such as MAPKs) are activated by osmotic stresses [1, 2, 33]. These protein kinases may be important components in the signal transduction pathway of various environment signals in plants under cold stress.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…6). These signalling cascades are important factors in modulating the acquisition of cold tolerance; for example, it was reported that MAPK3, MAPK4 and MAPKKK were induced following exposure to cold stress in Arabidopsos thaliana (Mizoguchi et al, 1996;Nakagami et al, 2005), and that exposure to cold acclimation markedly increased transcript levels of the MAPKKK16 gene in Dendrobium flowers (Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that exposure to conditioning/acclimation treatments activated various molecular mechanisms including TFs, hormone metabolism, signalling, stress genes, cellular redox status, ethylene production and lipid metabolism. For example, cold acclimation induced the following: AP2, NAC, WRKY and MYB TF genes in Bermuda grass and eucalyptus (Zhu et al, 2015;Gaete-Loyola et al, 2017); ABA signalling genes in olive, zucchini and eucalyptus (Guerra et al, 2015;Gaete-Loyola et al, 2017); reactive oxygen species (ROS) scavenging in olive and tomato (Guerra et al, 2015;Barrero-Gil et al, 2016); jasmonic acid biosynthesis pathways in Camelia (Li et al, 2016) and MAPK signalling in Dendrobium (Wu et al, 2016). In peach, LTC elevated ERFs and ethylene-synthesising enzymes' mRNA levels, as well as ethylene production thus enhancing fruit softening while considerably lowering internal browning symptoms (Tanou et al, 2017;Wang et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%